2022
DOI: 10.3390/pathogens11050551
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled, Multicenter Study to Evaluate the Safety and Efficacy of ThymoQuinone Formula (TQF) for Treating Outpatient SARS-CoV-2

Abstract: There is an urgent need for an oral drug for the treatment of mild to moderate outpatient SARS-CoV-2. Our preclinical and clinical study’s aim was to determine the safety and preliminary efficacy of oral TQ Formula (TQF), in the treatment of outpatient SARS-CoV-2. In a double-blind, placebo-controlled phase 2 trial, we randomly assigned (1:1 ratio) non-hospitalized, adult (>18 years), symptomatic SARS-CoV-2 patients to receive oral TQF or placebo. The primary endpoints were safety and the median time-to-sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
0
18
0
1
Order By: Relevance
“…The three doses of BSO were well tolerated, with only three subjects experiencing mild epigastric discomfort that settled down after taking the capsules after meals. Recently, a randomized phase II trial in COVID patients compared adverse events for patients who took TQ (3 g per day) or a placebo, and the results indicated that TQ was safe and tolerable [ 47 ]. Our four patients took only three tablets of 500 mg per day with no documented side effects, which is correlated with these previous data.…”
Section: Discussionmentioning
confidence: 99%
“…The three doses of BSO were well tolerated, with only three subjects experiencing mild epigastric discomfort that settled down after taking the capsules after meals. Recently, a randomized phase II trial in COVID patients compared adverse events for patients who took TQ (3 g per day) or a placebo, and the results indicated that TQ was safe and tolerable [ 47 ]. Our four patients took only three tablets of 500 mg per day with no documented side effects, which is correlated with these previous data.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in the rate of adverse events ( p = 0.16), indicating its safety, which is consistent with a previous Phase 1 study (Thomas et al, 2022). TQF significantly improved the total symptom burden faster ( p < 0.001), and increased cytotoxic CD4 + ( p = 0.04) and helper CD8 + ( p = 0.04) central memory T lymphocytes (Bencheqroun et al, 2022).…”
Section: Thymoquinone and Nigella Sativamentioning
confidence: 98%
“…TQ shows relatively high cytotoxicity in in vitro assessment of SARS-CoV-2 (hCoV-19/Egypt/NRC-03/ 2020) (Abdallah et al, 2022). TQ inhibits four further SARS-CoV-2 variants (Omicron, 614D, Delta, UK, Brazil) in infection of HEK293-ACE2 cells with an IC 50 value range between 1 and 3 µM (Bencheqroun et al, 2022). Compared with IC 50 of Nirmatrelvir at the nanomolar range (Rosales et al, 2022), these values seem F I G U R E 1 Chemical structures of anti-SARS-CoV-2 thymoquinone from Nigella sativa and other phytochemicals.…”
Section: In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…These trials examined suppression of Helicobacter pylori infections and dyspepsia, [147][148][149][150][151] parasitic, bacterial and human immunodeficiency virus infections, [152][153][154][155][156][157] hepatitis C symptoms, 158,159 and Candida albicans-induced vaginitis. 160 Other initial findings suggest that NS oil 161 and TQ 162 have potential to relieve SARS-2-COVID symptoms. 163,164 In addition, NS was evaluated for treating skin disorders, [165][166][167][168][169][170] for alleviating diverse oral health problems, [171][172][173][174][175][176][177][178] and for relieving menstrual-and menopausal-related symptoms.…”
Section: Cardiometabolic Risk Factorsmentioning
confidence: 99%